Detection of Candida albicans in Urine Patients of Diabetes Melitus using Polymerase Chain Reaction (PCR) Method - Exzora, Helmalia Bilqis; Qurrohman, Muhammad Taufiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Candida albicans is a dimorphic fungus that can grow in culture as a blastopore or as pseudohyphae. Laboratory diagnosis of the Candida albincans fungus can be carried out molecularly, which aims to identify DNA in the fungus being examined and carried out by going through the initial molecular stage, namely DNA isolation. The purpose of this study was to determine whether the fungus Candida albicans was present in urine isolate samples from diabetes mellitus sufferers at the Wonosari 1 Klaten Community Health Center. The research method used is descriptive. The samples used were urine samples from diabetes mellitus sufferers at the Wonosari 1 Community Health Center. Based on the research results, data analysis and discussion in this study, it can be concluded that the Candida albicans fungus can be detected in the ITS2 region at a product length of 107bp using the Polymerase Chain Reaction (PCR) method.